Nilai Total Ketidakteraturan Titik Pada Amalgamasi Graf Prisma - Junianto Sesa; La Ode Muhlis (Jurnal Matematika, Statistika dan Komputasi, 2023)
It is not possible to determine the total vertex of irregular strength of all graphs. This study aims to ascertain the total vertex irregularity strength in prismatic graph amalgamation for n>=4. Determination of the total vertex irregularity strength in prismatic graph amalgamation is done by ascertaining the largest lower limit and the smallest upper limit. The lower limit is analyzed based on the graph properties and other supporting theorems, while the upper limit is analyzed by labeling the vertices and edges of the prismatic amalgamation graph. Based on the results of this study, the total vertex irregularity strength in prismatic graph amalgamation is obtained, namely (4(P2,n))=2n , for n>=4.